Decisive Diagnosis of Seronegative Polyarthritis by 3-phase Bone Scintigraphy - Mirzaei, S.; Wagner, E.; Knoll, P.; Dunky, A.; Röhn, H. (Nuklearmedizin - NuclearMedicine, 1998)
Inflammatory joint disease is mainly diagnosed on grounds of clinical investigation, laboratory testing (acute phase reactants), and radiography. Radionuclide imaging has recently been added to the armamentarium of clinician. This case report points out the role of three-phase bone scan and HIG (human immunoglobulin) scan in the discovery of the inflammatory nature of polyarthralgia in a young woman with equivocal clinical and laboratory results. In the aim of diagnosing arthritis early in its course scintigraphy proved to be superior to conventional radiography. It also allows more discriminating selection of subsequent X-ray examination to limit radiation exposure.
Keywords: Seronegative polyarthritis; 99m-Tc MDP 3-phase bone scintigraphy; 99m-Tc HIG (human immunoglobulin) scan